2016
DOI: 10.1017/s1471068416000107
|View full text |Cite
|
Sign up to set email alerts
|

Enablers and inhibitors in causal justifications of logic programs

Abstract: To appear in Theory and Practice of Logic Programming (TPLP). In this paper we propose an extension of logic programming (LP) where each default literal derived from the well-founded model is associated to a justification represented as an algebraic expression. This expression contains both causal explanations (in the form of proof graphs built with rule labels) and terms under the scope of negation that stand for conditions that enable or disable the application of causal rules. Using some examples, we discus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In order to introduce information about negative literals in causal justifications, Cabalar and Fandinno (2017) extended causal justifications with a negation inspired by why-not provenance justifications (see Section 3.4; Damásio et al 2013). We now review this extension, starting with the introduction of negation in causal terms as follows:…”
Section: Explaining Negative Literals In Causal Justificationsmentioning
confidence: 99%
“…In order to introduce information about negative literals in causal justifications, Cabalar and Fandinno (2017) extended causal justifications with a negation inspired by why-not provenance justifications (see Section 3.4; Damásio et al 2013). We now review this extension, starting with the introduction of negation in causal terms as follows:…”
Section: Explaining Negative Literals In Causal Justificationsmentioning
confidence: 99%
“…Among these, Why-not Provenance Justifications (WnP) (Damásio et al 2013) share with our approach a semantic definition in terms of algebraic operations. A formal comparison was done in (Cabalar and Fandinno 2016a). With respect to (Pontelli et al 2009), a formal relation has not been established yet.…”
Section: Theoremmentioning
confidence: 99%
“…From a technical point of view, we have shown that our semantics is a conservative extension of the stable model semantics and that satisfy the usual desired properties for an LP semantics (casual stable models are supported models, minimal models in case of normal programs and can be iteratively computed by split table programs). It worth to mention that, besides the syntactic approaches to justifications in LP, the more related approach to our semantics is (Damásio et al 2013), for which a formal comparative can be found in (Cabalar and Fandinno 2016a) and that (Pontelli et al 2009) allows a Prolog system to reason about justifications of an ASP program, but justifications cannot be inspected inside the ASP program.…”
Section: Conclusion Related Work and Open Issuesmentioning
confidence: 99%